Slit-Robo signaling supports motor neuron avoidance of the spinal cord midline through DCC antagonism and other mechanisms - Nickerson, Kelsey R.; Sammoura, Ferass M.; Zhou, Yonghong; Jaworski, Alexander (Frontiers in Cell and Developmental Biology, 2025)
Axon pathfinding and neuronal migration are orchestrated by attractive and repulsive guidance cues. In the mouse spinal cord, repulsion from Slit proteins through Robo family receptors and attraction to Netrin-1, mediated by the receptor DCC, control many aspects of neural circuit formation. This includes motor neuron wiring, where Robos help prevent both motor neuron cell bodies and axons from aberrantly crossing the spinal cord midline. These functions had been ascribed to Robo signaling being required to counter DCC-mediated attraction to Netrin-1 at the midline, either by mediating repulsion from midline-derived Slits or by silencing DCC signaling. However, the role of DCC in promoting motor neuron and axon midline crossing had not been directly tested. Here, we used in vivo mouse genetics and in vitro axon turning assays to further explore the interplay between Slit and Netrin signaling in motor neuron migration and axon guidance relative to the midline. We find that DCC is a major driver of midline crossing by motor axons, but not motor neuron cell bodies, when Robo1 and Robo2 are knocked out. Further, in vitro results indicate that Netrin-1 attracts motor axons and that Slits can modulate the chemotropic response to Netrin-1, converting it from attraction to repulsion. Our findings indicate that Robo signaling allows both motor neuron cell bodies and axons to avoid the midline, but that only motor axons require this pathway to antagonize DCC-dependent midline attraction, which likely involves a combination of mediating Slit repulsion and directly influencing Netrin-DCC signaling output.